ANALISIS FRAMING: PEMBERITAAN MEDIA MASSA MENGENAI KEBIJAKAN LUAR NEGERI INDONESIA DALAM MENANGGAPI RIVALITAS AMERIKA SERIKAT DAN CHINA (2019-2022) - Jessica Martha; Adrianus Harsawaskita; Idil Syawfi; Valeria Tania Margono (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
In the second period of President Joko Widodo's government, Indonesia strengthened its cooperative relations with the United States and China through various agreements in the economy and other global issues. Indonesia's decision is influenced by many factors, both internal and external. According to Michael Brecher, in the process of foreign policy formulation, the mass media have a rol to convey and advocate for the general public regarding the government's stance towards certain issues. Through this research, the research team wanted to find out whether the mass media in Indonesia support Indonesia's foreign policy in responding to the rivalry between the United States and China? To answer this question, the research team used the foreign policy formulation system (Michael Brecher) and the framing analysis (Robert N. Entman). The study was carried out on 15 selected news stories from Kompas, The Jakarta Post, and Tempo. Based on the research conducted, the research team concludes that the news conveyed by the mass media in Indonesia shows their support for Indonesia's foreign policy, especially its neutral stance in the rivalry between the United States and China.